2020
DOI: 10.3846/btp.2020.12778
|View full text |Cite
|
Sign up to set email alerts
|

Employee Engagement and Remuneration Justice in Lithuania and Poland

Abstract: The aim of the article is the analysis of the relationship between work engagement and evaluation of remuneration justice in the context of the dimensions of organizational justice in Lithuania and Poland. The starting point for the research was the identification the essence of evaluation of remuneration justice from the perspective of management sciences. Conclusions drawn from the analysis of the views on organizational justice allowed to define the key aspects of remuneration justice necessary for a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Unfortunately, according to the research conducted, the level of employee involvement is not satisfactory (IZPO 21%, IZP 34%). The level of employee involvement in the organisation and work depends on many factors, mainly on the working conditions created by the employer and the resources provided (Juchnowicz et al, 2020;Mostafa, Abed El-Motalib, 2020). The research conducted showed that the most important factors that determine the level of involvement of public administration employees are fair remuneration, non-financial recognition from superiors, as well as an appropriate atmosphere among employees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, according to the research conducted, the level of employee involvement is not satisfactory (IZPO 21%, IZP 34%). The level of employee involvement in the organisation and work depends on many factors, mainly on the working conditions created by the employer and the resources provided (Juchnowicz et al, 2020;Mostafa, Abed El-Motalib, 2020). The research conducted showed that the most important factors that determine the level of involvement of public administration employees are fair remuneration, non-financial recognition from superiors, as well as an appropriate atmosphere among employees.…”
Section: Discussionmentioning
confidence: 99%
“…Employee engagement has a direct impact on their work performance and, therefore, on the results and success of the entire organization (Borst et al, 2020a). Of course, employee engagement and their motivation to work are influenced by many factors, which is the subject of many studies (Al-dalahmeh et al However, despite numerous studies available in the literature, there is still a certain gap related to research on involvement in the area of public administration (Borst et al, 2020a;Juchnowicz et al, 2020;Khusanova et al, 2021). This study will fill the gap in determining the level of commitment, especially since the WIGOR model will be used, which has not yet been used in public administration units.…”
Section: Introductionmentioning
confidence: 99%